Methyltransferase 3 Mediated miRNA m6A Methylation Promotes Stress Granule Formation in the Early Stage of Acute Ischemic Stroke - Si, Wenwen; Li, Yi; Ye, Shanyu; Li, Zhen; Liu, Yangping; Kuang, Weihong; Chen, Dongfeng; Zhu, Meiling (Frontiers in Molecular Neuroscience, 2020)
The modification of methyltransferase-like (METTL) enzymes plays important roles in various cellular responses by regulating microRNA expression. However, how m6A modification is involved in stress granule (SG) formation in the early stage of acute ischemic stroke by affecting the biogenesis processing of microRNAs remains unclear. Here, we established a middle cerebral artery occlusion (MCAO) model in rats and an oxygen-glucose deprivation/reperfusion (OGD/R) model in primary cortical neurons and PC12 cells to explore the potential mechanism between m6A modification and SG formation. The in vivo results showed that the level of infarction and apoptosis increased while SG formation decreased significantly within the ischemic cortex with improved reperfusion time after 2 h of ischemia. Consistent with the in vivo data, an inverse association between the apoptosis level and SG formation was observed in PC12 cells during the reperfusion period after 6 h of OGD stimulation. Both in vivo and in vitro results showed that the expression of METTL3 protein, m6A and miR-335 was significantly decreased with the reperfusion period. Overexpression of the METTL3 and METTL3 gene-knockdown in PC12 cells were achieved via plasmid transfection and CRISPR-Cas9 technology, respectively. Overexpression or knockdown of METTL3 in oxygen-glucose deprivation of PC12 cells resulted in functional maturation of miR-335, SG formation and apoptosis levels. In addition, we found that miR-335 enhanced SG formation through degradation of the mRNA of the eukaryotic translation termination factor (Erf1). In conclusion, we found that METTL3-mediated m6A methylation increases the maturation of miR-335, which promotes SG formation and reduces the apoptosis level of injury neurons and cells, and provides a potential therapeutic strategy for AIS.